Impact of weed management strategies on their growth, community composition, and yield of wet direct-seeded rice under alternate wetting and drying irrigation - M.K. A. Буйян; С. У. Буйя; M. A. Салек; A. Хатун (Вестник защиты растений)
Water management systems of wet direct-seeded rice (WDSR) and alternate wetting and drying (AWD) have proven to be effective resource-conserving (RC) technologies for rice production. However, weed management (WM) practice in RC technology has not been adequately addressed in the literature. This study aimed to investigate weed dynamics and integrated weed management strategies in WDSR under the AWD irrigation system. Two field experiments were conducted with seven weed management options over two consecutive growing seasons, 2009–2010 and 2010–2011, at the Bangladesh Rice Research Institute, Gazipur. Results showed that the weed species Scirpus juncoides, Echinochloa crus-galli, and Cynodon dactylon were the most important. By contrast, Fimbristylis miliaceae, Cyperus iria, and Lindernia floribunda seemed to belong to the least important group. Weeds that interfered up to 55 days after seeding had a significant impact on rice growth and yield. Over time, weed dominance ranking changed. The application of herbicides mefenacet+bensulfuron methyl and pyrazosulfuron ethyl along with one-hand weeding effectively reduced weed growth, leading to higher weed control efficiency and grain yield. These two treatments reduced the weed-related indices, and increased the crop resistance.